2011
DOI: 10.1007/978-3-642-21227-7_67
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Approach to Brain Extraction from Premature Infant MRI

Abstract: Abstract. This paper describes a novel automatic skull-stripping method for premature infant data. A skull-stripping approach involves the removal of non-brain tissue from medical brain images. The new method reduces the image artefacts, generates binary masks and multiple thresholds, and extracts the region of interest. To define the outer boundary of the brain tissue, a binary mask is generated using morphological operators, followed by region growing and edge detection. For a better accuracy, a threshold fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Nevertheless most algorithms have reported good results on par or better than previously published works. In particular, Daliri et al [29] have shown an improvement in SI values compared to Ghadimi et al [36]; Peporte et al [71] have also reported better performance of their approach compared to four publicly available brain extraction tools, namely, BrainSuite 6 , SPM8-Statistical Parametric Mapping 7 , FMRIB Software Library (FSL) 8 and MRIcroN 9 . Likewise, Mahapatra [58] has demonstrated better accuracy of their results in relation to the graph cut approach of Sadananthan et al [83] and other publicly available software like BET [97], BSE [89] and Hybrid Watershed Algorithm (HWA) [86] that is a part of FreeSurfer Software Suite 10 .…”
Section: Validation Of Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Nevertheless most algorithms have reported good results on par or better than previously published works. In particular, Daliri et al [29] have shown an improvement in SI values compared to Ghadimi et al [36]; Peporte et al [71] have also reported better performance of their approach compared to four publicly available brain extraction tools, namely, BrainSuite 6 , SPM8-Statistical Parametric Mapping 7 , FMRIB Software Library (FSL) 8 and MRIcroN 9 . Likewise, Mahapatra [58] has demonstrated better accuracy of their results in relation to the graph cut approach of Sadananthan et al [83] and other publicly available software like BET [97], BSE [89] and Hybrid Watershed Algorithm (HWA) [86] that is a part of FreeSurfer Software Suite 10 .…”
Section: Validation Of Resultsmentioning
confidence: 94%
“…Ghadimi et al [36] Similarity index [29] Similarity index Peporte et al [71] Dice metric, Jaccard metric, false positive, false negative Mahapatra [58] Dice metric, Jaccard index, sensitivity, specificity, false positive rate and Hausdorff distance 4.2.2.1. Atlas-based algorithms.…”
Section: Authors Validation Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuzzy rules were used to define the positions of the triangles. Peporte et al [23] Presented an approach called Hybrid Skull-Stripping (HSS). A binary mask was generated using morphological operators to define the brain tissue outer boundary, which was later followed by region growing and edge detection.…”
Section: Introductionmentioning
confidence: 99%